Tafsir Etika dan Tanggung Jawab Ilmuan - Ahmad Darlis; Ali Imran Sinaga; Ayau Ummad Nasution; Erra Malinda; Lisa Sersanawawi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2022)
Humans as religious and moral beings certainly realize that ethics is basically based on the moral values that he uses when interacting with his social environment, these values are also what he will later carry as the foundation and responsibility for disseminating knowledge and information to those around him. Science is very crucial for human life and will continue until the end of his life, nowadays every one of us realizes that science does not come by itself. Science that exists today is born from various theories and ideas of scientists' thinking, to give a definition of something, scientists/experts usually use two approaches, namely from the point of view of language and also in terms of terms or interpretation. Every scientist has his own interpretation of a science so that not all scientists have the same point of view, but these differences of opinion can actually advance the forefront of a science. Thus scientists have a great role and responsibility for the sciences and theories that he disseminates to the wider community, scientists not only spread knowledge but themselves as educated people must also reflect the ethics and responsibilities of a scientist. This research uses a research library sourced from the literature and also the interpretation of the verses of the Qur'an and Tafsir.